DNA damage, and repair in mutagenesis and carcinogenesis: implications of structure-activity relationships for cross-species extrapolation - Vogel, Ekkehart W.; Nivard, M. J. M.; Ballering, L. A. B.; Bartsch, Helmut; Barbin, A.; Nair, Jagadeesan; Comendador, M. A.; Sierra, L. M.; Aguirrezabalaga, I.; Tosal, L.; Ehrenberg, L.; Fuchs, R. P. P.; et al. (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 1996)
Previous studies on structure-activity relationships (SARs) between types of DNA modifications and tumour incidence revealed linear positive relationships between the log TD50 estimates and s-values for a series of mostly monofunctional alkylating agents. The overall objective of this STEP project was to further elucidate the mechanistic principles underlying these correlations, because detailed knowledge on mechanisms underlying the formation of genotoxic damage is an absolute necessity for establishing guidance values for exposures to genotoxic agents. The analysis included: (1) the re-calculation and further extension of TD50 values in mmol/kg body weight for chemicals carcinogenic in rodents. This part further included the checking up data for Swain-Scott s-values and the use of the covalent binding index (CBI); (2) the elaboration of genetic toxicity including an analysis of induced mutation spectra in specific genes at the DNA level, i.e., the vermilion gene of Drosophila, a plasmid system (pX2 assay) and the HPRT gene in cultured mammalian cells (CHO-9); and (3) the measurement of specific DNA alkylation adducts in animal models (mouse, rat, hamster) and mammalian cells in culture. The analysis of mechanisms controlling the expression of mammalian DNA repair genes (alkyltransferases, glycosylases) as a function of the cell type, differentiation stage, and cellular microenvironment in mammalian cells. The 3 classes of genotoxic carcinogens selected for the project were: (1) chemicals forming monoalkyl adducts upon interaction with DNA; (2) genotoxins capable of forming DNA etheno-adducts; and (3) N-substituted aryl compounds forming covalent adducts at the C8 position of guanine in DNA. In general, clear SARs and AARs (activity-activity relationships) between physiochemical parameters (s-values, 06/N7-alkylguanine ratios, CBI), carcinogenic potency in rodents and several descriptors of genotoxic activity in germ cells (mouse, Drosophila) became apparent when the following descriptors were used: TD50 estimates (lifetime doses expressed in mg/kg b.wt. or mmol/kg b.wt.) from cancer bioassays in rodents; the degree of germ-cell specificity, i.e., the ability of a genotoxic agent to induce mutations in practically all cell stages of the male germ-cell cycle of Drosophila (this project) and the mouse (literature search), as opposed to a more specific response in postmeiotic stages of both species; the Mexr−/Mexr+ hypermutability ratio, determined in a repair assay utilizing Drosophila germ cells; mutation spectra induced at single loci (the 7 loci used in the specific-locus test of the mouse (published data), and the vermilion gene of Drosophila); and doubling doses (DD) in mg/kg (mmol/kg) for specific locus test results on mice. By and large, the TD50 values, the inverse of which can be considered as measures of carcinogenic potency, were shown to be predictable from knowledge of the in vivo doses associated with the absorbed amounts of the investigated alkylators and with the second-order constant, kc, reaction at a critical nucleophilic strength, nc. For alkylating agents kc can be expressed as the second-order rate constant for hydrolysis, kH2O, and the substrate constant s: kH2OTD50 is a function of a certain accumulated degree of alkylation, here given as the (average) daily increment, ac, for 2 years exposure of the rodents. The TD50 in mmol/kg × day) could then be written: T−fsD50∗=ac×λkH2O×10ncs. This expression would be valid for monofunctional alkylators provided the reactive species are uncharged. This is the case for most SN2 reagents. Although it appears possible to predict carcinogenic potency from measured in vivo doses and from detailed knowledge of reaction-kinetic parameter values, it is at present not possible to quantify the uncertainty of such predictions. One main reason for this is the complication due to uneven distribution in the body, with effects on the dose in target tissues. The estimation can be improved by considering the distribution of dose in the body. In the present analysis, direct-acting alkylators were studied. It is evident that dosimetry and reaction-kinetic characterization of genotoxic metabolites would render it possible to predict the potency of precarcinogens as well.
Elektronische Reproduktion der Druck-Ausgabe 8. März 1999
Gesehen am 10.01.2024